2023
DOI: 10.1186/s12974-023-02744-7
|View full text |Cite
|
Sign up to set email alerts
|

Berberine ameliorates depression-like behaviors in mice via inhibiting NLRP3 inflammasome-mediated neuroinflammation and preventing neuroplasticity disruption

Abstract: Objectives Neuroinflammation has been suggested that affects the processing of depression. There is renewed interest in berberine owing to its anti-inflammatory effects. Herein, we investigated whether berberine attenuate depressive-like behaviors via inhibiting NLRP3 inflammasome activation in mice model of depression. Methods Adult male C57BL/6N mice were administrated corticosterone (CORT, 20 mg/kg/day) for 35 days. Two doses (100 mg/kg/day and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…induce the polarization of macrophages to the M1 phenotype and promote pyroptosis. , However, few studies have investigated the effects of macrophage pyroptosis on the surrounding parenchymal cells. It was reported that NLRP3 inflammasome activation in neurodegenerative diseases activated caspase-1 that shears the precursors of IL-1β to its mature forms. Meanwhile, caspase-1 cleaves Gasdermin D (GSDMD) or Gasdermin E (GSDME) to form pores that directly permeabilize the plasma membrane, consequently leading to rupture of the plasma membrane and release of the proinflammatory cellular contents, including matured IL-1β and IL-18, which induced inflammatory responses or initiated the process of inflammatory cell or parenchymal cell death. , Tan et al reported that DRD2 reprogrammed macrophages toward the M1 phenotype and induced pyroptosis via GSDME-mediated crosstalk . Subsequently, they found that cocultured M1 macrophages with breast cancer cells upregulated the expression of NLRP3, GSDME, and IL-1β and promoted pyroptosis of breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…induce the polarization of macrophages to the M1 phenotype and promote pyroptosis. , However, few studies have investigated the effects of macrophage pyroptosis on the surrounding parenchymal cells. It was reported that NLRP3 inflammasome activation in neurodegenerative diseases activated caspase-1 that shears the precursors of IL-1β to its mature forms. Meanwhile, caspase-1 cleaves Gasdermin D (GSDMD) or Gasdermin E (GSDME) to form pores that directly permeabilize the plasma membrane, consequently leading to rupture of the plasma membrane and release of the proinflammatory cellular contents, including matured IL-1β and IL-18, which induced inflammatory responses or initiated the process of inflammatory cell or parenchymal cell death. , Tan et al reported that DRD2 reprogrammed macrophages toward the M1 phenotype and induced pyroptosis via GSDME-mediated crosstalk . Subsequently, they found that cocultured M1 macrophages with breast cancer cells upregulated the expression of NLRP3, GSDME, and IL-1β and promoted pyroptosis of breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, rodent studies found fluoxetine reduced the CUMS elevated IL-1β in rat PFC (Pan et al, 2014), and the LPS elevated IL-1β, IL-6 and TNF-α in mouse hippocampus (Duda et al, 2017). On the other hand, drugs with anti-inflammatory properties, such as the Geraniol, Sinomenine, Patchouli alcohol, Baicalin and Berberine, alleviated the the CUMS and corticosterone-induced depressive-like behaviors in mice, respectively (Bai et al, 2023;Deng et al, 2015;He et al, 2023;Liu et al, 2018;Qin et al, 2023). Patchouli alcohol and Berberine take effect through inhibiting the NLRP3-mediated neuroinflammation (He et al, 2023;Qin et al, 2023), while Baicalin takes effect through inhibiting the toll-like receptor 4 expression via the PI3K/AKT/FoxO1 pathway (L. T. .…”
Section: Neuroinflammationmentioning
confidence: 96%
“…On the other hand, drugs with anti-inflammatory properties, such as the Geraniol, Sinomenine, Patchouli alcohol, Baicalin and Berberine, alleviated the the CUMS and corticosterone-induced depressive-like behaviors in mice, respectively (Bai et al, 2023;Deng et al, 2015;He et al, 2023;Liu et al, 2018;Qin et al, 2023). Patchouli alcohol and Berberine take effect through inhibiting the NLRP3-mediated neuroinflammation (He et al, 2023;Qin et al, 2023), while Baicalin takes effect through inhibiting the toll-like receptor 4 expression via the PI3K/AKT/FoxO1 pathway (L. T. . A recent study further showed Saikosaponin C alleviated the chronic social defeated stress (CSDS)-induced depressivelike behaviors in mice, through inhibiting the IL-6 methylation, which indicates the prominent role of epigenetic modulation of pro-inflammatory cytokines in depression (Bai et al, 2023).…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Berberine (BBR) stands out as a promising agent for combating neuroinflammation, effectively regulating the inflammatory response triggered by infections, toxins, aging, or ischemia-reperfusion through multiple signaling pathways [23,[90][91][92][93]. In an in vitro model simulating the pathology of Alzheimer's disease, BBR alleviates neuroinflammatory response by reducing the production of proinflammatory cytokines in microglia [94].…”
Section: Blockade Of Inflammatory Response and Necroptosismentioning
confidence: 99%